Decent work between economic growth and sustainable development - Lixandrão, Letícia; Branchi, Bruna A. (Revista Hipótese, 2020)
This paper discusses the contribution of decent work to sustainable development, following the eighth Sustainable Development Goal (SDG). Based on a literature review and research on Brazilian indicators' official website, it was possible to discuss the relationship between decent work, economic growth and sustainable development, and evaluate Brazil's position through an exploratory and descriptive research. As a result, a lack of available official indicators was identified. Also, the persistence of various types of pay inequalities, the growing unemployment rate, and young people's precarious situation continue to hamper progress towards the SDG 8.
Keywords: Decent work; 2030 Agenda; Indicators; Brazil